Histopathological study of the liver of Tyto alba owls - نهلة ابراهيم; مها شلفة; براءة حسن (Latakia University Journal -Biological Sciences Series, 2022)
The current study was conducted in the Graduate Studies Laboratory in the Biology Department ,Faculty of Science ,Tishreen University. It included histological morphological study of the liver of owls . The study showed that the liver occupies the upper right part of the thoracic-abdominal cavity. Its color is dark red. It weighs about (4.263-4.453)grams consisting of two main lobes (right and left),the right lobe is a little larger than the left one and both of them appear with full edges. The liver is surrounded by a very thin capsule of fibrous connective tissue .As the histological study of the liver showed that the septa between the lobules are not clear ,the multifaceted cells line up in the form of cords ,it has nuclei spherical near the center contains one nucleus or tow nuclei, Blood sinuses are abundant , the presence of adipocytes is observed clear around the blood sinuses and kuffer cells are located inside the sinuses and the borders of the endothelial cells, but for the porta distance ( hepatic triad ) is clear .